XLIV Esposizione Internazionale d'Arte - La Biennale di Venezia 1990 : Dimensione Futuro - L'artista e lo spazio - General Catalogue 1990. - XLIV Biennale di Venezia, 1990 (Venezia : La Biennale di Venezia, 1990)
Eric Andersen ; Giovanni Anselmo ; Arman Armando ; Frank Badur ; Nanni Balestrini ; Giacomo Balla ; Frida Baranek ; Per Barclay ; Gianfranco Baruchello ; Jean Bazaine ; Bernd e Hilla Becher ; Joseph Beuys ; Guillaume Bijl ; Roger Bissiere ; Alighiero Boetti ; Pierre Bonnard ; Georges Braque ; Marcel Broodthaers ; Daniel Buren ; Sylvano Bussotti ; William S. Burroughs ; George Brecht ; John Cage ; César ; Marc Chagall ; Giuseppe Chiari ; Eduardo Chillida ; Henning Christiansen ; Christo ; Leo Copers ; Philip Corner ; Dadamaino ; Wim Delvoye ; Stan Douglas ; Jean Dubuffet ; Marcel Duchamp ; Raoul Dufy ; Öyvind Fahlström ; Laszlo Feher ; Robert Filliou ; Alberto Giacometti ; Brion Gysin ; Hans Hartung ; Raoul Hausmann ; Dick Higgins ; Hi Red Center ; Jenny Holzer ; Anish Kapoor ; Raoul de Keyser ; Yves Klein ; Milan Knizak ; Arthur Köpcke ; Jirí Kolár ; Jeff Koons ; Shigeko Kubota ; Fernand Léger ; Markus Lüpertz ; David Mach ; René Magritte ; Alfred Manessier ; Piero Manzoni ; Nicola de Maria ; Henri Matisse ; La Monte Young ; François Morellet ; Reinhard Mucha ; Maurizio Nannucci ; Yoko Ono ; Robin Page ; Nam June Paik ; Panamarenko ; Benjamin Patterson ; Antoine Pevsner ; Francis Picabia ; Serge Poliakoff ; Julio Pacheco Rivas ; Dieter Roth ; Takako Saito ; Eric Satie ; Mario Schifano ; Rob Scholte ; Jana Sterbak ; Ernesto Tatafiore ; Jean Tinguely ; Tristan Tzara ; Emilio Vedova ; Jan Vercruysse ; Michel Verjux ; Wolf Vostell ; Robert Watts ; Franz West ; Marian Zazeela
XLIV Esposizione Internazionale d'Arte - La Biennale di Venezia, 27.05 - 30.09.1990 : Dimensione Futuro - L'artista e lo spazio
English
kunstcatalogus